A GEOCHEMICAL STUDY OF THE GROUNDWATER IN THE MISLI BASIN AND ENVIRONMENTAL IMPLICATIONS - Yuce G. (My University, 2007)
The aim of this study was to determine geochemical properties of groundwater and thermal water in the Misli Basin and to assess thermal water intrusion into shallow groundwater due to over-extraction. According to isotope and hydrochemical analyses results, sampled waters can be divided into three groups: cold, thermal, and mixed waters. Only a few waters reach water–rock chemical equilibrium. Thermal waters in the area are characterized by Na+–Cl−–HCO 3 − , while the cold waters by CaHCO3 facies. On the basis of isotope results, thermal waters in the Misli basin are meteoric origin. In particular, δ18O and δ2H values of shallow groundwater vary from −10.2 to −12.2‰ and −71.2 to −82‰, while those of thermal waters range from −7.8 to −10.1‰ and from −67 to −74‰, respectively. The tritium values of shallow groundwater having short circulation as young waters coming from wells that range from 30 to 70 m in depth vary from 10 to 14 TU. The average tritium activity of groundwater in depths more than 100 m is 1.59 ± 1.16, which indicates long circulation. The rapid infiltration of the precipitation, the recycling of the evaporated irrigation water, the influence of thermal fluids and the heterogeneity of the aquifer make it difficult to determine groundwater quality changes in the Misli Basin. Obtained results show that further lowering of the groundwater table by over-consumption will cause further intrusion of thermal water which resulted in high mineral content into the fresh groundwater aquifer. Because of this phenomenon, the concentrations of some chemical components which impairs water quality in terms of irrigation purposes in shallow groundwaters, such as Na+, B, and Cl−, are highy probably expected to increase in time.
Keywords: TURKEY; MISLI BASIN; GROUNDWATER; THERMAL WATER; HYDROCHEMISTRY; δ18O; δ2H; TRITIUM